THE ROLE OF PARENTS IN PROVIDING RELIGIOUS LITERACY TO CHILDREN THROUGH DA'WAH COMMUNICATION IN THE FAMILY ENVIRONMENT - Diarindiani, Ayu; Nuzuli, Ahmad Khairul; Rimin, Rimin (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2024)
This study aims to identify the role of parents in providing religious literacy to children through da'wah communication in the family environment. The method used in this study is descriptive qualitative with a phenomenological approach. The results of the study indicate that the role of parents is very important in providing religious literacy to children, especially in the family environment. Parents play an important role in providing religious literacy because parents are the first madrasah for children, moreover religious literacy covers moral and ethical values which will guide children in the future. The impact if parents are successful in providing religious literacy to children, the majority of informants said that if parents are successful in providing religious literacy, children will have good character, which children will also be easily directed, children will not easily fall into negative things. It cannot be denied that the influence in the current era is enormous. With the application of religious literacy, children are not easily affected by a bad environment. Religious literacy can also study daily life. Children will also understand and live life according to religious values and principles. Religious literacy is also a way of cultivating children's character. In which religious literacy has a role in forming the character of a person. Parents must also be able to utilize technological media such as mobile phones, reading media and other things that are also an effective method of providing religious understanding. In providing religious literacy, parents must also build good communication forums with children and also provide a comfortable and safe space for children. Because in fostering children's interest in studying religion, parents must be able to understand the nature, character and interests of children first, so that can reduce the failure of parents in providing religious literacy.